ANALISIS SEKTOR TERTINGGAL KABUPATEN TANJUNG JABUNG BARAT - Rati Purnama Sari; Ahmad Syukron Prasaja (Pusat Riset dan Publikasi, 2023)
Gross Regional Domestic Product (GRDP) growth by various industries can be leveraged to improve a country's economic performance. Regional Gross Domestic Product (GRDP) is one of the factors. It can be used to determine the economic level of a country or region based on current or fixed prices. Gross domestic product (GDP) growth in the region occurs when the region has major or base sectors with relatively high growth rates. The study uses time-series data from the Jambi Province Central Bureau of Statistics (BPS) from 2018 to 2021. The purpose of this study is to identify the key underdeveloped sectors and potential business opportunities in Tanjung Jabun Barat province from 2018 to 2021. 2018 was recorded before the outbreak of the Covid-19 pandemic and 2021 was recorded after the Covid-19 incident. This is done using location quotient analysis and dynamic location quotient (DLQ).